Digital Transformation – Meeting the Challenges 2018
DOI: 10.18690/978-961-286-170-4.3
|View full text |Cite
|
Sign up to set email alerts
|

Citizen adoption of e-government services – Evidence from Hungary

Abstract: Bled eConference, organized by University of Maribor, Faculty of Organizational Sciences, has been shaping electronic interactions since 1988. Bled eConference is the oldest, most traditional and well renowned conference in the field with more than 30 years of tradition. The theme of this year's conference is dedicated to "Digital Transformation -Meeting the Challenges".The evolution of digital technologies and solutions has significantly impacted the way in which business is conducted and have big implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
3
1
Order By: Relevance
“…The findings suggest that adoption strategies cannot exclude extensive stakeholder involvement in the roll-out of e-procurement within the Ghanaian milieu. In contrast to other studies (El-Masri and Tarhini, 2017; Aranyossy, 2018; Kunnapapdeelert and Pitchayadejanant, 2020), this study revealed that the construct H has a negative influence on the adoption decision of e-procurement systems in a developing country. The use of e-commerce is still relatively new, and government e-commerce is at its nascent stage in Ghana.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings suggest that adoption strategies cannot exclude extensive stakeholder involvement in the roll-out of e-procurement within the Ghanaian milieu. In contrast to other studies (El-Masri and Tarhini, 2017; Aranyossy, 2018; Kunnapapdeelert and Pitchayadejanant, 2020), this study revealed that the construct H has a negative influence on the adoption decision of e-procurement systems in a developing country. The use of e-commerce is still relatively new, and government e-commerce is at its nascent stage in Ghana.…”
Section: Discussioncontrasting
confidence: 99%
“…The study thus concludes that there is no significant relationship between Mobile Pay (MPAY) and Return on equity of deposit money banks in Nigeria. However, these findings discussed were not in conformity with results of Abaenewe., Ogbulu & Melugba (2013), Aranyossy (2018). But justified the findings of Barngetuny and Kimuton (2015) that examined the significant relationship mobile pay and return on equity of deposit money banks in Nigeria.…”
Section: Panel Error Correction Modelmentioning
confidence: 67%
“…First and foremost, the analysis covers e-government users' perspective from technology adoption and value creation at the same time. While an earlier analysis of Aranyossy (2018) already explored some aspects of e-government service adoption in Hungary, this combination of the theories of technology adoption and value creation represents a new approach. Secondly, our focus on actual usage instead of intent to use in the TAM/UTAUT context is potentially more relevant for practitioners and policy makers, while still rare (although not without example e.g., Sivathanu 2018).…”
Section: Research Modelmentioning
confidence: 99%